Exploring Possible Selves Through Sharing Stories Online: Case Studies of Preservice Teachers in Bilingual Classrooms. (May 2018) - Gaines, Rachel; Choi, Eunjeong; Williams, Kyle; Park, J. Hannah; Schallert, Diane L.; Matar, Lina
We examined how narrative was used in online classroom discussion as preservice bilingual teachers experimented with possible future selves. Considering associations between narrative and identity construction, we explored the complementary roles of stories from personal past experiences and backgrounds, experience as teacher interns, and imagined experiences of possible future selves as four preservice teachers endeavored to understand what it means to be a teacher of bilingual children. Data came from transcripts of nine computer-mediated discussions (CMDs) incorporated as a classroom activity in a theory-into-practice teacher preparation course. Findings suggest that preservice teachers' diverse trajectories to becoming bilingual and their motivations for becoming teachers as expressed in narratives during CMD have the potential to increase the specificity and diversity of possible selves for all discussion participants. Narratives shared in discussion allow all preservice teachers to borrow from a library of lived experiences to inform their imagined future teaching selves.